The Role of Macroeconomic factors on Sukuk Market Development of Gulf Cooperation Council (GCC) Countries - Al-raeai, Arafat Mansoor; Zainol, Zairy; Abdul Rahim, Ahmad Khilmy bin (International Journal of Economics and Financial Issues, 2018)
Macroeconomic factors are regional or national economic factors which externally impact the financial strategies of governments and corporations, including debt financing decisions. The literature related to the financial management acknowledges the significant role that macroeconomic factors play to determine the financial market development. The aim of this paper is to propose a conceptual model/framework for investigating the role of macroeconomic factors on Sukuk market development in Gulf Cooperation Council (GCC). GCC economies depend heavily on oil revenues which makes them subject to oil prices fluctuations. Therefore, GCC’s governments should diversify their economies by looking for Sukuk as an alternative source of financing, to cover their budget deficit, when the price of oil decreases, and reduce their reliance on oil, because Sukuk has advantages compared to the conventional bond particularly in terms of less information asymmetry. The prior studies have mostly focused on firms’ characteristics determinants of Sukuk issuances but gave a little consideration to the role of country’ characteristics on Sukuk market development. This paper proposes a framework to explain the main macroeconomic determinants of Sukuk market development with a focus on the GCC countries that have the largest region in terms of the Islamic financial assets. It is anticipated that the outcome will support policymakers to improve the current state of Sukuk market. Keywords: Sukuk, Macroeconomic Variables, GCC countries JEL Classification: E6